Design of Sex Education (SESI) Dolls as A Media for Preventing Sexual Violence Against Preschool Children - Nova Ari Pangesti; Mugihartadi Mugihartadi; Donna Syania Anggraeni; Khoirun Nisa (GLOBAL HEALTH SCIENCE GROUP, 2024)
Child sexual violence cases are still a serious problem and have long been a hot topic of discussion at the national and international levels. Children are more vulnerable to becoming victims of sexual violence because children generally lack knowledge so they do not understand the importance of protecting their body parts. The high number of cases of sexual violence against children shows the importance of educational media as a medium for preventing sexual violence against children. However, the problem is that in society sex education is still often considered taboo to talk about. Many parents misunderstand sex education so that sex education is often considered unnecessary to be taught to early childhood. Designing SESI (Sex Education) dolls as a medium for preventing sexual violence against preschool children. This study uses Research and Development (R&D). The sample that will be used for the feasibility test and product effectiveness test in this study are 3 media experts in Mechanical Engineering or Mechatronics, 3 material experts by Child Nursing Lecturers, and 10 Grantung Kindergarten students. Data collection methods using observation, interviews and questionnaires Product development and product feasibility testing are used to analyze data. According to the feasibility test, 3 material experts overall obtained an average score of 87.7 with recommendations of Very Good